Expectancy In connection with hepatic hematoma of traumaUe origin: primary experience. - Gastambide, Carmelo; Croci, Fabio; Ruiz Liard, Alfredo; Trostchansky, José; Crosa, Jorge (Cirugía del Uruguay, 1984)
Even nowadays, hepatlc leslonll caused by cloae al,, dominal traumatism present a high morblmort1:1llty rate and has suggested the necessity of revlewln9 the the, rapeutic approach.